Quality Management in Developing Student Competencies in Madrasas/Schools - Firman; Febrineng (STMIK Indonesia Banda Aceh, 2025)
Education is a form of human culture that develops and changes through teaching and training. This education coexists with changes occurring in the culture of life. Religious education taught in madrasas/schools may not necessarily inspire harmonious change in life. Teachers are required to monitor the quality of learning and implement quality management that impacts students. Quality management is a system that can transform the quality of an organization, thereby creating member satisfaction and improving organizational performance. To improve the quality of madrasas/schools, the primary focus is improving the quality of learning within the institution itself. Law No. 20 of 2003 states that learning is the process of interaction between students, teachers, and learning resources in a learning environment. The author's data analysis focused on library research, utilizing library sources including books, scientific articles, journals, e-books, and other documents relevant to the research being studied.